2016
DOI: 10.1002/jcla.22102
|View full text |Cite
|
Sign up to set email alerts
|

A rapid and simple liquid chromatography-tandem mass spectrometry method for the measurement of testosterone, androstenedione, and dehydroepiandrosterone in human serum

Abstract: It is demonstrated that a reliable, simple, sensitive and potential method for steroids assay in clinical laboratories had been successfully developed by LC-MS/MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…Nevertheless, it has been reported that the combination of an effective serum processing method such as optimized SPE and a sensitive LC-MS/MS instrument increased the assay performance, allowing a low quantification limit well below that reported for the androgens (T, A4, and DHEA) in female serum. 27,28 In this study, we employed a relatively simple serum preparation method and were able to completely separate and accurately quantitate the T, A4, DHEAS, DHT, and 17-OHP with a LC-MS/MS procedure in 6.5 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it has been reported that the combination of an effective serum processing method such as optimized SPE and a sensitive LC-MS/MS instrument increased the assay performance, allowing a low quantification limit well below that reported for the androgens (T, A4, and DHEA) in female serum. 27,28 In this study, we employed a relatively simple serum preparation method and were able to completely separate and accurately quantitate the T, A4, DHEAS, DHT, and 17-OHP with a LC-MS/MS procedure in 6.5 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…A sensitive, simple and robust LC-MS/MS method for the simultaneous quantification of seven androgen-and estrogen-related steroids in post-menopausal serum. The Journal of Steroid Biochemistry and Molecular Biology, 144, 523-534. https://doi.org/10.1016/j.jsbmb.2014.08.015 positive-mode APCI (Gao et al, 2015;Gibson et al, 2019;Legacki et al, 2020;Xu et al, 2017) and APPI (Desai et al, 2019;Handelsman et al, 2020;Keski-Rahkonen et al, 2015)…”
Section: Mobile Phase and Separation Conditionsmentioning
confidence: 99%
“…The relative “cleanliness” of the plasma and serum matrices allows some investigators to rely on protein precipitation alone to prepare samples for LC–MS/MS. Not surprisingly, the most frequently used solvents include methanol (Broccardo et al, 2013; McCulloch & Robb, 2017; Xu et al, 2017) and acetonitrile (Subhash Chandra Bose et al, 2013; Genangeli et al, 2017). The relevance of this approach is emphasized by the fact that most testosterone in circulation is protein bound (Tai et al, 2007).…”
Section: Matrices and Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, the research eld in which the lanthanide complexes were used as biosensors has a great interest. [20][21][22][23][24][25][26][27][28][29][30] Luminescent optical biosensor Tb (atorvastatin) 3 (Tb-Ator) complex embedded in PEG matrix have many advantages over the mentioned traditional methods. The chemical structure of atorvastatin is presented in Fig.…”
Section: Introductionmentioning
confidence: 99%